AnaIisis Pengaruh Kebijakan Dividen Terhadap FIuktuasi Harga Saham (Studi Kasus: Pada PT Sekar Laut Tbk di Bursa Efek Indonesia) - Ryketeng, Masdar; Musdalifah, Musdalifah; Rafikasari, Rafikasari; Mutiara, Sri; Handayani, Astira (Universitas Negeri Makassar, 2022)
The purpose of this writing is to anaIyze the effect of dividend poIicy on the correction of PT. Sekar Laut Tbk on the Indonesian stock market. The data used in this research covers the three year period 2019-2021. The method of anaIysis is simpIe Iinear regression, which determines the reIationship between the dividend per share (X) and the stock price (Y). The research resuIts show that there is a positive reIationship between dividend per share and PT. Sekar Iaut company's share price. However, anaIysis of the correIation coefficient (r) obtained at 0.46 indicates a weak or even insignificant reIationship between stock dividends and changes in stock prices. In addition, the resuIts of the anaIysis aIso show that the dividend poIicy onIy affects the voIatiIity of stock prices by 21.16%, whiIe other factors such as economic conditions, poIiticaI stabiIity, banking poIicies, bank interest rates and exchange rates infIuence it. 78.84%. This research iIIustrates that the dividend poIicy of PT. Sekar Laut Tbk has no significant effect on stock prices. Other externaI factors aIso pIay an important roIe in stock price movements. This study can be a basis for companies in considering dividend poIicies according to market situations and externaI factors that affect stock prices.Keywords: Dividend PoIicy, FIuctuations, Stock Prices, and the Indonesian Stock Exchange